New apparatus for skid testing : assessment for dusty surfaces - Chik, Abdul Aziz; Che Puan, Othman; Ismail, Che Ros (Faculty of Civil Engineering, 2003)
Skidding has been identified as one of the most common factor for road accident. Skid resistance is also related to several road features, which are the skidding properties of the road surface, the presence of water and contaminants. Many apparatus are designed and has been used to determine the value of the skid property of a road surface under dry and wet conditions. The purpose of this research is to design and fabricate a new apparatus for measuring the skid resistance on dusty surfaces. Calibration and verification have been carried out and two correlation charts are plotted. This research is based on downstream application, i.e. calibration and correlation are carried out with specific condition to have a related function of the conventional test method (British Pendulum Tester) with the new tester. From the results, significant drop of skid number are recorded when loose particles are applied to the samples surfaces. This shows that there is a possibility of skid assessment through friction turning mechanism. However, the tester requires further modification to achieve higher consistency.